Response to Comment on "Is the nuclear refractive index lower than cytoplasm? Validation of phase measurements and implications for light scattering technologies": A Comment on "How a phase image of a cell with nucleus refractive index smaller than that of the cytoplasm should look like?", e201800033. Issue 6 (2nd May 2018) - Steelman, Zachary A.; Eldridge, Will J.; Wax, Adam
Abstract : Recently, Maxim A. Yurkin commented on our paper "Is the nuclear refractive index lower than cytoplasm? Validation of phase measurements and implications for light scattering technologies" as well as on a complementary study "Cell nuclei have lower refractive index and mass density than cytoplasm" from Schürmann et al. In his comment, Yurkin concluded that quantitative phase images of cells with nuclei that are less optically dense than the cytoplasm must exhibit a characteristic concavity, the absence of which is evidence against our conclusion of a less‐dense nucleus. In this response, we suggest that Yurkin's conclusion is reached through an oversimplification of the spatial refractive index distribution within cells, which does not account for high index inclusions such as the nucleolus. We further cite recent studies in 3‐dimensional refractive index imaging, in which the preponderance of studies supports our conclusion. Finally, we comment on the current state of knowledge regarding subcellular refractive index distributions in living cells. Abstract : A Comment on "How a phase image of a cell with nucleus refractive index smaller than that of the cytoplasm should look like? ", e201800033